The Effect of Effective Tax Rate (ETR), Tunneling Incentives, Audit Quality and the Independent Board of Commissioners on Indications of Transfer Pricing for Manufacturing Companies Listed on the IDX for the 2021-2023 Period - Anggraeni, Fitri Aprilya; Astuti, Tutut Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The impact of effective tax rates (ETR), tunnel incentives, good corporate governance (GCG) (measured by audit quality and an independent committee on the pricing of listed manufacturing companies), and the Indonesia Stock Exchange on securities listed on the stock exchange were researched using quantitative techniques in this study. A total of 202 manufacturing businesses listed on the Indonesia Stock Exchange between 2021 and 2023 are the population of this study. A total of 81 businesses that were sampled in the study were selected using a purposeful selection technique. To evaluate the hypothesis, SPSS version 25 is used in conjunction with multiple linear regression analysis. The results of this study show that ETR, Tunneling Incentives, and the Independent Board of Commissioners have a negative effect on Transfer Pricing, while the Audit Committee has no effect on Transfer Pricing.